the Effect of sun breakers characteristics on wind noise - Al-Jawadi, Miqdad Haider; Askar, Samar hilal (Iraqi Journal of Architecture and Planning, 2018)
In hot regions like Iraq, where solar energy is very high, sun breaks are preferred to be implemented in design of the buildings as apart of the facade. Some types of sun breakers cause whistling noise or other types of noise which annoy occupants of the building especially if the building is residential. as it has been found, numbers of sun breakers may act similar in preventing sun ray penetration, therefore classified these shapes according to it’s effects on causing noise may help designers in choosing the shapes matching there esthetic needs with less noise generating. Thus sun breakers with different shapes has been studied in this research using cfd program to predict the noise which caused by each type of sun breakers using forced wind on them in different directions.The results showed that’s possible to provide designers with clear picture on the behavior of sun breakers on noise generating in order to prevent the annoy ones.